Plunder of Namibian Uranium (United Nations, 1980)
Portrait of black man with mining helmet, superimposed with map of Namibia Poster advertising the United Nations hearings on the plunder of Namibian Uranium, held in New York, 7-11 July, 1980 PO-1480